Combined molecular dynamics, STD-NMR, and CORCEMA protocol yields structural model for a UDP-galactopyranose mutase–inhibitor complex. Issue 6 (15th March 2015) - Shi, Yun; Ardá, Ana; Pinto, B. Mario
Graphical abstract: Abstract: UDP-galactopyranose mutase (UGM) is an enzyme involved in the biosynthesis of the Mycobacterium tuberculosis cell wall, and is essential for the growth and survival of the organism. A micromolar inhibitor developed by tetrafluorination of the UGM substrate has been previously studied by saturation transfer difference (STD) NMR spectroscopy. To elucidate the bioactive conformation of the inhibitor bound to UGM, we employ molecular dynamics (MD) simulations to construct a structural model. The MD model is subsequently validated by a good fit between experimental and theoretical STD effects, the latter calculated by a complete relaxation and conformational exchange matrix (CORCEMA) analysis. This structural model is used to explain the relative binding affinities of the inhibitor and the parent substrate.